The Black Experience from African Roots to the Black Identity in America: - Timucin Bugra EDMAN; Hacer GOZEN (ACROSS)
The people of Africa were dragged to the New World, where they were enslaved and put to work and starved to death. The atrocities that African people witness are ongoing even today. This paper aims to take a journey through the history of African people. The article is divided into two parts: the first part is a concise history of the Atlantic Slave Trade and of its cultural and sociological aftermath in the New World, where the struggle between the South and the North exploited African Americans even after the Civil War. The second part focuses on the literary production of the African people, in order to connect these with experiences defined by pain, agony and nostalgia.